Clinical and genetic features of Koreans with retinitis pigmentosa associated with mutations in rhodopsin - Jung, Young Hoon; Kwak, Jay Jiyong; Joo, Kwangsic; Lee, Hyuk Jun; Park, Kyu Hyung; Kim, Min Seok; Lee, Eun Kyoung; Byeon, Suk Ho; Lee, Christopher Seungkyu; Han, Jinu; Lee, Junwon; Yoon, Chang Ki; et al. (Frontiers in Genetics, 2023)
Purpose: To investigate the clinical features, natural course, and genetic characteristics of Koreans with rhodopsin-associated retinitis pigmentosa (RHO-associated RP). Design: We conducted a retrospective, multicenter, observational cohort study. Participants: We reviewed the medical records of 42 patients with RHO-associated RP of 36 families who visited 4 hospitals in Korea. Methods: Patients with molecular confirmation of pathogenic variants of the RHO gene were included. The patients were divided into two subgroups: the generalized and sector RP groups. A central visual field of the better-seeing eye of < 10° or a best-corrected visual acuity of the better-seeing eye < 20/40 indicated the progression to late-stage RP. Results: The mean age at which symptoms first appeared was 26.3 ± 17.9 years (range: 8-78 years), and the mean follow-up period was 80.9 ± 68.7 months (range: 6-268 months). At the last follow-up visit, the generalized RP group showed a significantly higher rate of visual field impairment progression to late-stage RP than that of the sector RP group (22 of 35 [62.9%] vs. 0 of 7 [0.0%], P = 0.003). No cases in the sector RP group progressed to generalized RP. Best-corrected visual acuity deterioration to late-stage RP was observed only in the generalized RP group (13 of 35 patients; 37.1%), whereas no deterioration was observed in the sector RP group. We identified 16 known and three novel RHO mutations, including two missense mutations (p.T108P and p.G121R) and one deletion mutation (p.P347_A348del). The pathogenic variants were most frequently detected in exon 1 (14 of 36 [38.9%]). The most common pathogenic variants were p.P347L and T17M (5 of 36 [13.9%] families). Among 42 patients of 36 families, 35 patients of 29 families (80.6%) presented with the generalized RP phenotype, and seven patients of seven families (19.4%) presented with the sector RP phenotype. Three variants (p.T17M, p.G101E, and p.E181K) presented with both the generalized and sector RP phenotypes. Conclusions: This multicenter cohort study provided information on the clinical and genetic features of RHO-associated RP in Koreans. It is clinically important to expand the genetic spectrum and understand genotype-phenotype correlations to ultimately facilitate the development of gene therapy.